2023
DOI: 10.53560/ppasb(60-1)776
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study Elucidating Associated Predictors in Postpartum Depression among Pakistani Women

Abstract: Postpartum depression is a psychological condition that deteriorates a mother’s cognitive health and overall family functioning. This survey-based cross-sectional study was done on postpartum mothers between 15-40 years of age to determine the epidemiology of postpartum depression in Pakistan. Edinburg postnatal depression scale (EPDS) and an adapted relationship assessment tool were used to determine the prevalence of postpartum depression. A total of n=103 responses were collected from different regions of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The prevalence rate of PPD in Pakistan ranges from 28% to 63%, making it the highest among Asian countries ( Aliani & Khowaja, 2017 ). A recent study showed a 67.96% prevalence of PPD in Pakistan ( Zulfiqar et al, 2023 ), which is approximately four times higher than the worldwide prevalence rates. This can be attributed to several factors such as cultural norms (responsibility for household chores prioritized over own well-being, joint family system, postpartum customs), gender inequality, the stigma surrounding mental health, and socioeconomic factors such as poverty and limited access to healthcare services ( Gulamani, Shaikh & Chagani, 2013 ; Rahman, 2007 ).…”
Section: Introductionmentioning
confidence: 94%
“…The prevalence rate of PPD in Pakistan ranges from 28% to 63%, making it the highest among Asian countries ( Aliani & Khowaja, 2017 ). A recent study showed a 67.96% prevalence of PPD in Pakistan ( Zulfiqar et al, 2023 ), which is approximately four times higher than the worldwide prevalence rates. This can be attributed to several factors such as cultural norms (responsibility for household chores prioritized over own well-being, joint family system, postpartum customs), gender inequality, the stigma surrounding mental health, and socioeconomic factors such as poverty and limited access to healthcare services ( Gulamani, Shaikh & Chagani, 2013 ; Rahman, 2007 ).…”
Section: Introductionmentioning
confidence: 94%
“…Social support, encompassing emotional, instrumental, and informational assistance from one's social network, is pivotal in shaping the postpartum experience. The cultural context significantly influences the nature and availability of social support, impacting how women navigate the challenges of PPD (Zulfiqar et al, 2023). The intricacies of social relationships, family structures, and community norms in Pakistan contribute to a unique landscape for examining the intersection of postpartum depression and social support (Sabiha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%